Slow inward barium current and contraction on frog single muscle fibres. - Potreau, D (1980)
1. Excitation-contraction coupling process in isolated frog muscle fibres, under conditions which allow the development of a Ba permeability, has been investigated by the simultaneous recording of electrical and mechanical activity. 2. The sustained contraction elicited by a long lasting Ba action potential depends on two mechanisms. The first is potential dependent, the second which is inhibited by MnCl2 (10 mM), depends on the inward flux of Ba ions. 3. The relationship observed between the inward IBa and the peak tension resembles that which has been observed between ICa and the contraction on other muscular structures. 4. The relative tension progressively declines as the intracellular Ba concentration increases and the contractility ends after a series of depolarizing pulses (or Ba action potentials). This indicates that the Ba ions which enter the cell release Ca ions and replace them in the intracellular storage sites. 5. Following a pretreatment with caffeine, the inward IBa fails to induce a contraction. Moreover a muscle which has been loaded with barium until the contraction ceases, does not develop a contracture in presence of caffeine. These results show that the Ba induced Ca release is located at the level of the sarcoplasmic reticulum. 6. Calculations show that the amount of Ba ions necessary to abolish the contractility corresponds to the maximum ability of the sarcoplasmic reticulum for Ca binding. 7. Almost all the inward flux of Ba ions and the contraction are abolished by glycerol-treatment which suggests that the coupling occurs at the T-system level. The results are discussed in regard to the technical limitations of the voltage-clamp method.